Numerical study on the energy performance of an axial-flow pump with different wall roughness - Chen, Yuling; Sun, Qing; Li, Zhixiang; Gong, Yan; Zhai, Jianwei; Chen, Huixiang (Frontiers in Energy Research, 2022)
Pumping stations play an important role in China's South-to-North Water Diversion, agricultural irrigation, and municipal drainage. Some pumping station units have been put into operation for a long time with the improper operation and requiring maintenance. Moreover, the surface of the flow components has been worn and corroded leading to the increase of relative roughness and a decrease of the hydraulic performance efficiency of the pumping station units. In this paper, we performed field measurements and numerical simulations to study the influence of wall roughness on the hydraulic performance of the slanted axial flow pump device under multiple working conditions. The effects of the wall roughness of the impeller chamber on the hydraulic performance of the pump, the guide vane chamber, and the inlet and outlet flow channel have been investigated. Among them, the wall roughness has the largest influence on the hydraulic performance of the pump and the smallest influence on the inlet and outlet flow channel. For the devices with different roughness on the impeller chamber wall in different flow rate conditions, the performance of the pump device goes worse in the large flow rate condition, and the device performance is better in the small flow condition and designed flow condition. The efficiency of the slanted axial flow pump device decreases significantly as the increment of flow rate. In the same flow rate condition, the performance of the device with Ra = 5 μm is similar to that with a smooth wall, where Ra is the roughness of the wall. With the increase of roughness, the uniformity of axial velocity distribution coefficient decreases, and velocity-weighted average drift angle increases. External characteristic parameters such as torque and the static pressure on the blade pressure surface are gradually decreasing with the increment/decrement of xxx. The large roughness can induce the instability of wall flow and enhance the turbulent kinetic energy near the blade surface.